Coronary versus carotid artery plaques. Similarities and differences regarding biomarkers morphology and prognosis. (April 2018) - Sigala, Fragiska; Oikonomou, Evangelos; Antonopoulos, Alexis S; Galyfos, George; Tousoulis, Dimitris
Highlights: Carotid and coronary artery disease are two major artherosclerotic conditions. Atherosclerotic plaque development in both locations share similar characteristics. However differences exist regarding risk factors, plaque biology and progression. These differences dictate the different use of diagnostic modalities and treatment goals. Abstract : Carotid and coronary artery disease are two major atherosclerotic conditions that have shown an increased prevalence in the last three decades that is associated with high morbidity and mortality. Recent data have revealed that the development of the atherosclerotic plaque — the basic entity in both diseases — may share similar characteristics and mechanisms irrespective of the location site. Even though the biology of atherosclerotic process is similar, there are differences in plaque morphology and characteristics. Indeed, plaque erosion, calcified nodules, fibrous cap thickness and macrophage accumulation may be different in the setting of coronary and carotid artery disease. The perivascular adipose tissue surrounding the coronary arteries (but not carotids) could also affect plaque biology. In this review we focus on comparative the characteristics of both types of atherosclerotic plaques and summarize existing knowledge to provide useful conclusions about current and future treatment strategies.